Mengelola risiko layanan digital: kasus gangguan m-banking pada BSI - Shofiranti, Najwa Ishma (Maliki Interdisciplinary Journal, 2025)
Digital transformation in the banking sector has brought convenience and efficiency of services to customers, but has also given rise to new challenges in the form of increasingly complex cyber risks. This article discusses the case of a digital service disruption experienced by Bank Syariah Indonesia (BSI) in May 2023 as a real example of the vulnerability of the banking system to ransomware attacks. The disruption had a wide impact, not only technically, but also on reputation and compliance with personal data protection regulations. Through a descriptive-qualitative approach based on literature studies, this article identifies various types of digital risks and formulates risk management strategies that include strengthening system security, emergency response readiness, crisis communication, diversification of service channels, and increasing digital literacy. Collaboration between banks, regulators, and cybersecurity authorities is also emphasized as an important step to strengthen the resilience of the national financial system in the ever-evolving digital era.